INOVASI BENTUK PERTUNJUKAN KESENIAN RAKYAT KUDA LUMPING DI DESA GANDU II, KECAMATAN TEMBARAK, KABUPATEN TEMANGGUNG - Nur Rokhim (Abdi Seni, 2020)
Fever of collaboration with Leakan folk art in Temanggung apparently cannot be stopped anymore. Senior artists on average rejected the presence of the collaboration, they felt uncomfort-able with the development of such performance art. Finally, the Office banned the collaboration of Kuda Lumping with Leak, Pendet and Barong Balinese dances. This is intended to restore the existence of the Horse Lumping show as before as an art that has the characteristics of Temanggu-ng. Sri Budoyo’s Lumping Horse Art is in a complicated situation, amidst the increasingly diverse demands of people’s tastes. The determination of the public to support art has been unanimous to preserve and preserve Kuda Lumping art so that it still exists with its trademark. Various problems of partners as a result of the inclusion of art outside the region that disturbs the existence of local art as a regional characteristic, then solutions will be offered to overcome the problems encoun-tered. Innovation is a way to be done as a solution. The innovation made is the empowerment of children as the next generation of Kuda Lumping arts in the village of Gandu II, who look forward to taking control of the arts in the village. The children were given Geculan dance training as a basis for their dance, movements arranged according to their age.Keywords: Innovation, Folk Art, Kuda Lumping.